Le son et l’image - Philippe Nieto (Criminocorpus)
Since the first third of 19th Century, a kind of broadseet has been circulating in France, devoted to news items, criminal news items : the canard. These fact sheets have the distinction of containing a printed lament which distinguishes them from the periodicals of news items which arise at the same time. This article analyzes the role and the place of the image in the canard and its links with the printed sheet and the lament, in the general context of a new approach to crime, to the victim against the backdrop of the infatuation with the criminal news item and the birth of detective story.